RESPONSE OF SOYBEAN (Glycine max Merr.) TO VARIATIONS IN TYPE AND FREQUENCY OF PGPR APPLICATION - Baihaqi, Achmad Fachrurijal; Saylendra, Andree; Ritawati, Sri; Rohmawati, Imas (Universitas Veteran Bangun Nusantara, 2025)
Soybean (Glycine max Merril.) is a strategic food crop whose productivity must be improved to meet increasing national demand. The use of Plant Growth Promoting Rhizobacteria (PGPR) offers a promising approach to enhance plant growth and yield. This study evaluated the effects of PGPR types and application frequencies on the growth and yield of the Grobogan soybean variety. The experiment, conducted from June to September 2025, employed a two-factor Randomized Complete Block Design with five PGPR types and three application frequencies. Results showed that PGPR type significantly affected plant height, leaf number, and pod number, while application frequency significantly influenced plant height at 10 WAP and pod number. Bamboo root PGPR produced the best performance, with a plant height of 78.84 cm, 43 leaves, and 110 pods under three applications. These findings demonstrate that bamboo root PGPR is a promising biological agent for sustainably improving soybean productivity.